2017
DOI: 10.4028/www.scientific.net/msf.888.348
|View full text |Cite
|
Sign up to set email alerts
|

Radiation Damage Study of Electrical Properties in GaN LEDs Diode after Electron Irradiation

Abstract: Nitride-based light emitting diodes (LEDs) is an attractive material due to its high temperature tolerance and suitable to be used in extreme environment. The irradiation process of Gallium Nitride (GaN) diode was carried out by electron irradiation with 1000 kGy and 1500 kGy doses with a conveyor speed of 50 kGy per pass. Capacitance-voltage (C-V) and current-voltage (I-V) characterization for both pre and post irradiation samples was done. Both current and capacitance show decreasing while reverse leakage cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…5 In recent years, many researchers investigated the radiation hardness of InGaN-based photoelectric devices like light emitting diodes (LEDs) under γ ray, electron, neutron, and proton radiation sources. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Regarding proton radiation, some studies have investigated the effect of radiation on LED performance from relatively low to very high proton energies. 7,[15][16][17][18][19][20] B. J. Kim et al investigated the optical and electrical performance of InGaN/GaN blue LEDs with 340 keV proton irradiation; they found that the optical performance was much more sensitive to proton irradiation compared to the electrical performance.…”
mentioning
confidence: 99%
“…5 In recent years, many researchers investigated the radiation hardness of InGaN-based photoelectric devices like light emitting diodes (LEDs) under γ ray, electron, neutron, and proton radiation sources. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Regarding proton radiation, some studies have investigated the effect of radiation on LED performance from relatively low to very high proton energies. 7,[15][16][17][18][19][20] B. J. Kim et al investigated the optical and electrical performance of InGaN/GaN blue LEDs with 340 keV proton irradiation; they found that the optical performance was much more sensitive to proton irradiation compared to the electrical performance.…”
mentioning
confidence: 99%
“…The capacitance decreases after irradiation whereas the reverse current rises. LEDs were irradiated with electrons at 1000 and 1500 kGy [14]. Samples were evaluated for the capacitance and voltage characteristics both before and after irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] In recent years, many researchers investigated the radiation hardness of InGaN-based photoelectric devices, such as solar cells and light emitting diodes (LEDs), under the radiation sources of γ rays, electrons, neutrons, and protons. [14][15][16][17][18][19][20][21][22][23][24][25][26][27] In terms of proton radiation, the research on InGaN solar cells is very few. Many studies dedicated to investigating the radiation effect on LED performance from relatively low to very high proton energies.…”
mentioning
confidence: 99%